2007
DOI: 10.1134/s000629790708007x
|View full text |Cite
|
Sign up to set email alerts
|

Pentaspan membrane glycoprotein, prominin-1, is involved in glucose metabolism and cytoskeleton alteration

Abstract: This study constitutes the first report revealing the participation of prominin-1 in glucose metabolism and cytoskeleton alteration. Upon stimulation with high glucose, the expression of prominin-1 was up-regulated with concomitant down-regulation of its phosphorylation. Prominin-1 mutated at its phosphorylation site inflicted a global change in the expression of several genes associated with glucose metabolism in L6 myotube cells. Further, the over-expression of prominin-1 promoted glucose uptake in these cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Supporting the aerobic glycolysis of cancer cells first reported by Otto Warburg in the 1950s [68], it was recently established that CD133 expression is associated with high cellular glucose metabolism: CD133 was found to be a glucose responsive gene in L6 myotubes [11] and CD133 expression to be concomitant to high glucose cellular uptake in U251 glioma cells [12]. Since co-localization of glucose transporters with the TfR in intracellular vesicles has previously been observed [69], [70], [71], whether CD133 can regulate iron uptake together with glucose transport by modulation of endocytosis remains an important question.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Supporting the aerobic glycolysis of cancer cells first reported by Otto Warburg in the 1950s [68], it was recently established that CD133 expression is associated with high cellular glucose metabolism: CD133 was found to be a glucose responsive gene in L6 myotubes [11] and CD133 expression to be concomitant to high glucose cellular uptake in U251 glioma cells [12]. Since co-localization of glucose transporters with the TfR in intracellular vesicles has previously been observed [69], [70], [71], whether CD133 can regulate iron uptake together with glucose transport by modulation of endocytosis remains an important question.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, AC133, a glycosylated epitope of CD133 protein initially associated with embryonic stem cells [8] and a variety of somatic stem cells, was extensively described as a putative cancer stem cell marker in blood, brain, colon, prostate, lung, breast, liver, and skin cancers [9], [10]. Other investigations revealed that CD133 is linked to cell metabolism as a glucose responsive gene in myotubes [11], as well as providing evidence for bioenergetic stress [12] and of non-exposure to high oxygen tension in gliomas (Bourseau-Guilmain et al, submitted).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in a conditional ablation model, tamoxifen-induced ablation of Prom1-expressing cells caused body weight loss ( 9 ). Studies have pointed to the potential involvement of Prom1 in cellular metabolism in rat myotubes and mouse pancreatic islets with contrasting findings ( 29 , 30 ), and an increase in Prom1 expression in young mice with induced obesity has been reported ( 31 ). In other respects, PROM1 was shown to promote glucose uptake in a human hepatocellular carcinoma cell line ( 32 ).…”
mentioning
confidence: 99%
“…These results support the findings of other authors such as Immervoll et al (24), whose data indicated that CD133 is involved in cellular polarity and is required for cellular movement as well as the processes of chemotaxis, embryonic development, invasive growth and metastasis. In addition, Yang et al (25) reported CD133 involvement in glucose metabolism and cytoskeleton alteration. Additionally, Rappa et al (7) showed that the downregulation of CD133 resulted in retarded cell growth, reduced cell motility and a decreased ability to form spheroids under stem cell-like growth conditions.…”
Section: Discussionmentioning
confidence: 99%